Study of heat transfer and friction loss of nanofluid suspension flow in square pipe heat exchanger / Jayprasanth Krishnan - Jayprasanth , Krishnan (2020)
An experimentational analysis was done to evaluate heat transfer features of graphene oxide (GO) nanofluid inside the cross section of square cross tube that was exposed to a uniform constant heat flux of the test segments. Lately huge figures of researches have been are proceeded out to examine the outcome of nanofluid in augmentation of the heat transfer rate in numerous heat exchangers particularly using hummer method to attain GO. In this case, advanced hummer method was used to obtain GO and further analyses the effect of the nanofluids. The viscosity and thermal conductivity for the (GO) nanofluids at the concentrations of 0.025%, 0.05%, 0.075%, and 0.1 wt % fixed similarly together with distilled water or known as distilled water before proceeding to the experiments. The heat transfer analysis of the flowing distilled water was compared with (GO) nanofluids using advanced hummer methods. The convective heat transfer coefficient of (GO)-distilled water nanofluid is greater than the base fluid by roughly from 9.7% to 32.7%. Furthermore, the heat transfer coefficient of the (GO)-distilled water enlarged as the flowrate rises. The increase in the pressure drop valued from 13.43% to 36.55%. The friction factor also surges as the values verified from 0.71% to 2.3%. The analysis reveals that more concentration leads to greater heat transfer coefficient, pressure drop and including friction factor.